Instruction on the Appropriate Utilisation of Antibiotics to Safeguard the Community Against the Threat of Resistance - Zorosisti Racohet; Shirgidi Sarakop (Akademi Sertifikasi Profesi Internasional, 2024)
Irrational drug utilisation has emerged as a global issue, with around 50% of medicationsbeing prescribed, distributed, marketed, and utilised incorrectly by patients. The primaryconcern with the irrational use of medications pertains to the inappropriate application ofantibiotics, which includes unsuitable drug types, incorrect dosages, prolonged administration,and excessive usage in non-bacterial infections. This syndrome induces antibiotic resistance.Individuals frequently use various antibiotics to address non-infectious ailments such ascoughs, influenza, and fevers without a physician's prescription, and these medications arereadily available at certain health institutions that lack comprehension of the requirements. Thisinitiative aims to inform the public about the hazards associated with the incorrect use ofantibiotics. This community outreach initiative involved counselling and video screeningsaround antibiotic usage in DAGUSIBU. We evaluated the activity's success by administeringpretests and distributing posters to the participating community. We determined the overallpercentage of individuals who could accurately answer questions. The data processing resultsindicate a rise in public comprehension and awareness of antibiotic resistance followingcounselling sessions.